A new species of Minooa Yamanaka, 1996 (Lepidoptera, Pyralidae) from Xizang, China - Qi, Mujie; Zuo, Xinghai (Zootaxa, 2021)
A new species of the genus Minooa Yamanaka, 1996 is described from Xizang Autonomous Region, China. Minooa longisacca sp. nov. can be easily distinguished from its congeners in the male genitalia by the sclerotized, short, bifurcated process at the base of the sacculus and the medial ridge connecting the apex of sacculus and base of costa of valva dentate and with a short thorn-like process at apex of ridge. DNA barcodes of all the Chinese species are provided along with illustrations of adult and genitalia and an updated key to all the species of Minooa worldwide.